Architecture and Pandemics - Design Studio Assignment and interdisciplinary contributions to a healthy unity for Covid-19 - Martins, Afonso Nuno (2022)
Among our guest authors are academics from different disciplines and professional experience. From the psychologists Rosa Afonso and Margarida Lima, passing through the infectious disease specialist who lived through the pandemic in a hospital environment António Maio, to Isabel Calado, with her focus on visual culture, and finally to UBI professors Miguel Santiago Fernandes, an architect with vast professional and pedagogical experience. To hey all accepted the pioneering challenge of relating architecture and covid-19, thus embarking on this exploratory interdisciplinary journey. This academic experience and its main results necessarily reflect a still-hot view, with SARS-Cov 2 cases and deaths still on the rise in many countries. Still, it may be useful to keep the debate going. After having reached a promising control of the virus impacts, thanks to the massive vaccinations programs, it is about time to understand to what extent we, as a society, can do better regarding hospitals and healthcare unities’ infrastructures; and, accordingly, investigate, in between the intersection of complementary field of study and the very history and grounds of the architectural discipline, how the pandemic could permeate architecture